Editorial de la revista número 4 del año 2017 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2017)
In the Letter to the Editor, Carolina Roni and Lic. Natalia Rosli describe the formation of a mentoring team for doctoral students in the Health Sciences PhD Program at the Instituto Universitario del Hospital Italiano.The off-label use of medications, that is, prescribing a drug outside the conditions specified in the product label, may expose patients to potentially futile, costly, and harmful treatments, and physicians to possible litigation. Augusto Ferraris analyzes the factors related to the off-label prescription of rituximab, an immunomodulatory agent, over a six-year period.Colloid cysts (CC) are benign tumors most frequently located at the roof of the third ventricle. Daniela Massa analyzes the experience of the Neurosurgery Service in the endoscopic resection of third-ventricle colloid cysts over a two-year period.Agustín Matías Muñoz presents a case of bone marrow transplantation in a patient with acute myeloid leukemia and disseminated Fusarium infection.Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma. It typically presents as a rapidly growing mass, with or without “B” symptoms (fever, night sweats, and weight loss). Tomás Richards reports an atypical case presenting as a painful, persistent ulcerated lesion on the gums, associated with rapid local bone destruction.Luis Alejandro Boccalatte and Eduardo Luis Mazzaro present imaging findings of an ectopic parathyroid adenoma, which after months of elusive search was located anterior to the T1 and T2 vertebrae.In the “Hospital Italiano in Medline” section, César Meller reviews the international experience in ultrasound screening for open spina bifida in the first trimester of pregnancy, focusing on the mid-sagittal view of the fetal head at 11–13 weeks.High-density lipoproteins (HDL) are remarkably heterogeneous in composition, structure, metabolism, and function. Patricia Sorroche discusses the relationship between poor glycemic control and altered HDL composition and function in patients with type 2 diabetes.María Florencia Grande Ratti and Bernardo Martínez describe the characteristics of the crowding or saturation phenomenon in the Emergency Center.Solar polymorphic erythema is the most frequent photodermatosis and typically appears in spring with the first intense sun exposure. María Manuela Martínez Piva describes a typical case of solar polymorphic eruption that responded appropriately to photoprotection measures.